LncRNA DLEU1 Contributes to the Growth and Invasion of Colorectal Cancer via Targeting miR-320b/PRPS1 - Xu, Dong; Yang, Fei; Fan, Yongchao; Jing, Wanling; Wen, Jianfei; Miao, Wen; Ding, Xiaoyan; Yang, Hongbao (Frontiers in Oncology, 2021)
Growing evidences suggest that long non-coding RNAs (lncRNAs) are closely correlated to the development of human cancer, such as colorectal cancer (CRC). A previous report suggested that DLEU1 accelerated CRC development. However, DLEU1's underlying mechanism in CRC remains unclear. In our study, the level of DLEU1 in CRC tissues is investigated by qRT-PCR. Our data exhibited that DLEU1 level was observably increased in CRC tissues and CRC cell lines and was closely associated with bad prognosis of CRC patients. CRC cell proliferation was repressed by sh-LncRNA DLEU1, whereas cell apoptosis was markedly stimulated. Moreover, knockdown of DLEU1 inhibited cell migration and invasion. Mechanistically, through interacting with miR-320b in CRC, DLEU1 promoted the level of PRPS1 which was a target of miR-320b. The rescue experiment confirmed that knockdown of DLEU1 repressed cell proliferation, migration and invasion while stimulated cell apoptosis via miR-320b / phosphoribosyl pyrophosphate synthetase 1 (PRPS1) axis. Meanwhile, the data of xenograft model exhibited that inhibition of DLEU1 suppressed tumor growth in vivo. In summary, DLEU1 knockdown may repress PRPS1 expression via miR-320b, and then repress cell proliferation, migration and invasion while stimulate cell apoptosis. Our research may provide a novel target for the treatment of CRC.